Physical and training characteristics of mixed martial arts athletes: Systematic review - Andrade A. (2019)
Copyright © National Strength and Conditioning Association.Mixed Martial Arts (Mma) Is A Combat Sport With Different and Complex Characteristics. The Purpose of The Review Is to Analyze Physical and Training Characteristics of Mma Athletes Through A SysTematic Review. The Search Was Performed In Electronic Databases Where 30 Articles Were Selected. The Mma AthLetes Must Have Strength, Power, Flexibility, Aerobic and Anaerobic Conditioning. Diet, Abrupt Weight Loss, Injury, and Psychological Aspects Merit Additional Attention In Future Studies. A Video Abstract Describing This Article Can Be Found In Supplemental Digital Content 1 (SEE VIDEO, HTTP://LINKS.LWW.COM/SCJ/A244).